How national is the national ballet syllabus? - Mijares, Clarissa Cecilia R. (2005.)
Thesis (B.M.)--University of the Philippines, Diliman.
This study looks into the history and evolution of the Philippine Ballet syllabus. The extent of reception and adoption of the syllabus by the Filipino dance community is likewise presented in this thesis as gathered from the opinions, perceptions, attitudes and impressions of the syllabus' authors, regional organizers and students.
Keywords: Dance -- Instruction and study